Pemilihan Tema Tugas Akhir Prodi Sistem Informasi Menggunakan Kolaborasi Metode Analytic Hierarchy Process (AHP), Simple Additive Weighting (SAW), dan SMART - Aditya Pratama; Septi Andryana; Ira Diana Sholihati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Completing the final project is a graduation requirements for a student to do. Many students take final project but don't have a theme for that. There are also students who take the theme of their final project but they are not in line with grades and abilities. On this issue, a research will be assist the National University Information System students in choosing theme of their final project which is processed using collaborative method of Analytical Hierarchy Process, Simple Additive Weighting, and Simple Multi-Attribute Rating Technique. This research begins by determining the criterion value of each student which calculated using SAW method for weight grades and SMART method for weight of ability, then looking for alternative values for each theme of the final project using the AHP method, the ranking process is carried out the multiplication matrix between the criteria and alternative which will produce optimal final project theme.